BUKTI MEDIS VERSUS BUKTI HUKUM - Sampurna, Budi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Medicine and Law are pragmatic and empiric activities which need evidences to prove the truth.  Both evidences are based on probability, but  medicine – particularly in evidence based medicine -  tends to apply a scientific standard of proof, one that is claimed more certain than the standards of proof courts apply in civil and criminal proceedings. On the other hand, medicine is also called as the art of probability and the science of uncertainty.
Keywords: medical; legal; evidence